Clitics and operators in the verbal domain in Mazahua (oto-manguean) - Mora-Bustos, Armando (2023)
The article presents the set of morphemes that are anchored on the nucleus. The informative and grammatical content of the clause has been distributed in prosodic phrases. The position of the morphemes that expresses grammatical functions within the verbal domain indicates whether they are enclitics or proclitics; thus, those that are located to the left of the verb are realized as operators, and those that are located to the right encode grammatical information. The article proposes that grammatical features such as polarity, modality classes, quantification types, movement forms, aspectual and temporal values are operators; clitics appear individually or in a cluster. Clitics is restricted by prosodic criteria; it presents fixed positions; it does not duplicate; it does not exhibit cumulative values; it occurs with different semantic value; only some meanings of the same group covary systematically. Clitic clusters are composed of four proclitics and four enclitics attached to the nucleus of the clause; the number of clitics is determined by the grammatical requirements generated in the grammatical context.